The Impact of Total Quality Management Toward the Employee Performance with Compensation as Moderating Variable(Case Study: BNI Syariah Pekalongan) - Desy Adella(2013113004) (Jurusan S-1 Ekonomi Syariah FEBI IAIN Pekalongan, 2017)
xii THE IMPACT OF TOTAL QUALITY MANAGEMENT TOWARD THE EMPLOYEE PERFORMANCE WITH COMPENSATION AS MODERATING VARIABLE (Case Study: BNI Syariah Pekalongan) By: Desy Adella ABSTRACT This research aimed to test the impact of total quality management (TQM) toward the employee performance with compensation as moderating variable. Case study in BNI Syariah Pekalongan. The data was collected by distributing questionnaires to the respondents. The Samples which used on this study are the employees of BNI Syariah Pekalongan with total sample of 40 respondents. The method analysis used to this study are multiple and moderated regression analysis. From the results of multiple regression test, there is one hypotheses that influence to the employee performance: total quality management has a significant effect towards the employee performance. Meanwhile, another hypothese with moderated regression analysis does not influence to the employee performance. This is compensation and TQM interaction which has no significant effect to the employee performance. Keywords: Total Quality Management, Compensation and Employee Performance.